FORMATION PRACTICE OF TRAFFIC-CALMING ZONES IN CITIES - Arsenieva, N.; Fomenko, G. (Municipal economy of cities. Series: «Economy science», 2022)
The increasing intensity of the flow of traffic flows to lead to problems due to the increased number of road transport facilities. How to certify the tribute to the Light Bank Ukraine spends up to 5 bln. dollars through road transport facilities. In 2020, the strategy was praised as a method of bringing national indicators of safe road traffic to the mid-European level of a significant increase in street and road barriers and road infrastructure. The new Strategy emphasizes the importance of designing streets and roads for the sake of safety and not security. It is important to develop more accessible systems and attachments for cars to help reduce accident rates, both for drivers and passengers and for others. It is also necessary to ensure safe traffic on the streets and roads with projects and control of security. Peace of mind can be reached for the change of street fences and technical entrances. The fragmentation of the standard in Ukraine is important to the fact that a complex approach was laid in the new before the creation of a system of careless minds rush along the streets of the city. They are being used to calm the traffic, as they are being installed not only for changing the speed, but as the main rank of the evenness of traffic flows. Particular respect is given to businessmen de car traffic conflicts with pedestrians and cyclists. So respect for the next respect for those who, when designing zones of calm, comfortable street and design of their space, may have important meanings that are looked at, as if you enter the mode of traffic of transport entrances. Calming zones further enhance the differentiation of road network elements according to the functions they perform. As shown by the analysis of foreign literature, the peace of mind can be classified and presented in 13 broad categories. The category of combined buildings and buildings is dependent on the characteristics of the traffic of transport facilities and the features of the design of the street and road barriers. Successful victorious entry in a calm environment led to the development of the victorious program in rich places of the country world. The establishment of principles of calming the traffic is to allow improving the geometrical parameters of the streets, changing the speed of the traffic and maximizing the benefits for pedestrians, cyclists and public transport.